Caracterização imunoproteômica dos antígenos de Leishmania (Leishmania) infantum, L. (L.) amazonensis e L. (Viannia) braziliensisdetectados pela técnica de imuno-histoquímica - Bruna Soares de Souza Lima (2013)
Leishmaniasis are caused by flagellate parasites of the genus Leishmania and are among the main endemic diseases of the world. The leishmaniasis can be subdivided, depending on parasite species and host immune response into five main clinical forms: localizated cutaneous, diffuse cutaneous, disseminated cutaneous, mucocutaneous and visceral, which is the most severe form of leishmaniasis, may be fatal if left untreated. Different diagnostic methods are used for confirmation of the disease, among which we can mention: parasitological, molecular and immunological. Although the parasitological diagnosis be sure, the definitive diagnosis, in most cases, results from the combination of these different methods. One of the parasitological methods used in pathology laboratory foridentification of Leishmania amastigotes in tissue samples of patients (biopsies) is the immunohistochemistry technique. Tafuri et al., 2004 demonstrated a immunohistochemistry diagnosis for canine visceral leishmaniasis, that according to the authors this is an technique as efficient as routine, but less expensive. Therefore, this work is justified for a better understanding of this methodology by identifying reactive proteins that makes this test able to be used in both clinical forms: ATL and VL. To this, protein extracts of Leishmania species were fractionated in to 2-DE gels followed by western blot using serum on technique recommended by Tafuri et al.,2004. The reactive spots in each species and all species simultaneously , were selected to identification by MS. Among the proteins identified, two were common to the three species, hsp 70 and -tubulin, and six were specific to L. amazonensis, nine to L. braziliensis and four to L. infantum. Some of these proteins have been described in the literature because of its antigenicity, whereas others appear to be new antigens, which could be targets of future studies for developing alternative diagnostic test.